The role of virtual reality and artificial intelligence in marketing relationship communications - Ferreira, M. M. (2021)
Virtual Reality (VR) and Artificial Intelligence (AI) have benefited from a constant presence in the front stage of the top technological breakthroughs due to their potential contribution in the Marketing field. This growing interest to understand the potential of VR and AI and as a new way to attract customers and enrich their experiences led to this study. Using the Integrated Marketing Communications concept, the final goal is to discuss the extent to which experiences using Virtual Reality and Artificial Intelligence may impact a customer experience in three different points of the customer journey: pre-purchase (brand associations), purchase (intention) and post- purchase stage (brand loyalty).